„TOTE WISSENSCHAFT”? – THOMAS VON AQUIN ALS KOMMENTATOR VON DE ANIMA I - Hellmeier, Paul D. (Divus Thomas, 2015)
In his critical edition of Aquinas’s commentary on the De Anima (1984), Father Gauthier observed that Thomas’s commentary was mostly ‘dead science’. Gauthier claimed that Aquinas wrote his commentaries on Aristotle in order to gather useful data for his theological research; however, when he was writing his commentary on the De anima, Aquinas had already written some philosophical remarks on the soul in his Summa Contra Gentiles. Why then did Aquinas also write a commentary? The author shows that Aquinas always grasps Aristotle’s text, even though he offers a different interpretation from that of many contemporary Aristotle scholars. Aquinas understood perfectly that the doxographical analyses of the opinions of Aristotle’s predecessors (De Anima I) have a deep philosophical meaning: these opinions constitute aporiai from which the dialectical inquiry into the principles of psychology must start. In other words, this doxographical section has not been included in his commentary merely to refute mistaken conceptions of the soul (e.g. to refute the Presocratics’ materialism) in order to defend an orthodox understanding of the soul. Nella sua edizione critica del commento di Tommaso al De Anima (1984) padre Gauthier osservava che il commento di Tommaso era, per larga parte, “scienza morta”. Gauthier ha notoriamente sostenuto che Tommaso scriveva i propri commenti ad Aristotele per avere dati a sostegno della propria ricerca teologica; tuttavia, al momento di redigere il commento al De Anima, l’Aquinate aveva già vergato pagine di psicologia filosofica nella Summa Contra Gentiles. Perché dunque scrivere un commento? L’autore dimostra che Tommaso ha sempre una conoscenza approfondita del testo che commenta, anche se offre una interpretazione diversa da quella proposta da molti interpreti contemporanei di Aristotele. Tommaso capiva perfettamente che le analisi dossografiche delle opinioni dei pensatori che precedettero Aristotele (De Anima I) hanno una profonda rilevanza filosofica: sono aporie da cui l’indagine (dialettica) sui principi di psicologia deve partire. In altre parole, questa sezione dossografica non è semplicemente inserita per confutare idee erronee circa l’anima (come ad esempio il materialismo dei presocratici), al fine di offrire una difesa ‘filosofica’ di una trattazione ortodossa dell’anima.